Maximum Power Point Tracking Algorithms for Grid-Connected Photovoltaic Energy Conversion System - J.Surya Kumari; Ch. Saibabu (Institute of Advanced Engineering and Science, 2013)
As the use of energy is increasing, the requirements for the quality of the supplied electrical energy are more tighten. Energy is the most basic and essential of all resources. As conventional sources of energy are rapidly depleting and the cost of energy is rising, photovoltaic energy becomes a promising alternative source. Photovoltaic (PV) generation is becoming increasingly important as a renewable source since it exhibits a great many merits such as cleanness, little maintenance and no noise. The output power of PV arrays is always changing with weather conditions, i.e., solar irradiation and atmospheric temperature. Therefore, a Maximum Power Point Tracking (MPPT) control to extract maximum power from the PV arrays at real time becomes indispensable in PV generation system. In recent years, a large number of techniques have been proposed for tracking the maximum power point (MPP). MPPT is used in photovoltaic (PV) systems to maximize the photovoltaic array output power, irrespective of the temperature and radiation conditions and of the load electrical characteristics the PV array output power is used to directly control the dc/dc converter, thus reducing the complexity of the system. The resulting system has high-efficiency. This paper presents in details comparison of most popular MPPT algorithms techniques which are Perturb & Observe algorithm(P&O) and Improved Perturb & Observe algorithm(IPO). Improved Perturb & Observe algorithm (IPO), is a very promising technique that allows the increase of efficiency and reliability of such systems. Modeling and designing a PV system with Improved Perturb & Observe algorithm (IPO) is remarkably more complex than implementing a standard MPPT technique. In this paper, Improved Perturb & Observe algorithm (IPO), system for PV arrays is proposed and analyzed.